Medical Illustration - A Pictorial Essay Visual Illustration of Obstetric Anal Sphincter Injuries (OASIS) Degrees of Severity, a Picture is Worth a Thousand Words - Abdugadir M. Abdulrahman (Journal of Coloproctology, 2024)
Obstetric anal sphincter injury affects about 5.7% of primiparous women who deliver vaginally. Perineal injury during childbirth is a common event with important morbidity associated with third-and-fourth degree perineal tears (also referred to as obstetric anal sphincter injuries—OASIS). As there was a lack of consistency in the classification of a partial anal sphincter injury, with up to 33% of consultant obstetricians classifying a complete or partial tear of the EAS as a second-degree tear. We have proposed simple, digital diagrammatic drawings to visually represent all degrees (grades) of OASIS based on the WHO OASIS classification.